2015
DOI: 10.1590/1678-4499.0050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth regulators application on the quality maintenance of 'Brookfield' apples

Abstract: The main goal of the present study was to elucidate the effect of growth regulators at harvest and postharvest quality of 'Brookfield' apples stored under controlled atmosphere through a multivariate approach. Thus, an experiment with two steps (field and storage) was carried out. The treatments in field were applied with an output of 1,000 L ha -1 of water. The following treatments were tested: Control: only water application; AVG (aminoethoxyvinylglycine): 0.83 kg ha -1 of Retain  applied 30 days before har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…1a). This result demonstrates that the combination of NAA plus AVG presents a response that is completely different from the other treatments, regarding the quality maintenance during the postharvest period, in accordance to the results verified by Brackmann et al (2015a). Figure 1.…”
Section: Quality Analysis After Eight Months Of Storagesupporting
confidence: 87%
See 4 more Smart Citations
“…1a). This result demonstrates that the combination of NAA plus AVG presents a response that is completely different from the other treatments, regarding the quality maintenance during the postharvest period, in accordance to the results verified by Brackmann et al (2015a). Figure 1.…”
Section: Quality Analysis After Eight Months Of Storagesupporting
confidence: 87%
“…3e). Brackmann et al (2015a) found higher percentage of healthy fruit in the AVG and AVG plus NAA treatment in comparison to the control and AVG plus Ethephon.…”
Section: Postharvest Quality Of 'Brookfield' Applementioning
confidence: 70%
See 3 more Smart Citations